Use of Puffery in Advertisements and its Effect on Consumer Attitude: An Empirical Study in Pune City - Dr. Surbhi Jain, Shivani Dorge (International Journal of Advanced Science and Technology, 2020)
Advertisements today have developed to be an essential part of the socio-economic system ofsociety. Puffery is an advertising type which praises the product that needs to be advertisedby  means  of opinions  that are rather  subjective,  overemphasizedand  mostly, affirming  no particular  facts.  Advertisements  every  so often  possess  puffery withmetaphorsthat appear to be significant but in realityoffervery little information. Consumers’ responses to these metaphorsrely  on the way they perceive themselves to be relatively knowledgeable about the item than others whom the advertisements is explicitlyexpected to encourage. When an advertisementis shown in a professional weekly or monthlywhich  is mostlyread  by experts  in the product  area,  puffery  in generalintensifies  the  effectiveness  of  the  advertisements.  When  readers  consider  they know as much as or more than over-all consumers, puffery cutsdown the effectiveness of the advertisements.  Furthermore,  the media  setting through  which  an advertisement  is shown  has a direct effect on decisionstaken  by consumers  who recognizethemselves  to have much  lesser  knowledge  regarding  the product  or an item that is promoted.  This paper demonstratesin  what way puffery advertisement  affects the attitude of consumers towards a product  and by what means  the firms are using their skillsand  methods  for increasing the pressure on consumers to buy a product that is being promoted.